2017
DOI: 10.1007/s00020-017-2369-7
|View full text |Cite
|
Sign up to set email alerts
|

Hadamard Multipliers on Spaces of Holomorphic Functions

Abstract: Abstract. Several representation theorems of multipliers are derived: in terms of analytic functionals, and germs of holomorphic functions. The co-induced topology via the representation theorems is discussed. As an application of the representation theorems the density of non-invertible multipliers is proved. Moreover, Euler differential operators are distinguished among all multipliers.Mathematics Subject Classification. 30H10, 46F15, 44A35, 30B40.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…This is precisely the equation which we obtained in (42). Therefore the same choice of f and the sequences p N n will lead to a contradiction.…”
Section: Proof Of Theorem 3 Assume That There Exists a Continuous Prmentioning
confidence: 54%
See 1 more Smart Citation
“…This is precisely the equation which we obtained in (42). Therefore the same choice of f and the sequences p N n will lead to a contradiction.…”
Section: Proof Of Theorem 3 Assume That There Exists a Continuous Prmentioning
confidence: 54%
“…These are the operators the associated matrix of which is just diagonal. This research was continued by Domański et al [15] and also by Vogt in [44,45] for spaces of distributions, in [43] for spaces of smooth functions and by Trybu la in [42] for spaces of holomorphic functions. In [14] and [16] Domański and Langenbruch showed that this theory provides the correct framework to study Euler's equation.…”
Section: Introductionmentioning
confidence: 94%
“…We only mention the articles which have had some impact on our research. This includes the results by Albanese, Bonet and Ricker [2][3][4][5], Bonet, Lusky and Taskinen [10,11], Bonet and Domański [9], Bonet and Taskinen [12] and also Trybuła [43]. Some of this research concerns Toeplitz operators on weighted sup-norm spaces.…”
Section: Main Theoremmentioning
confidence: 99%
“…В пространстве 𝐻(Ω) всех голоморфных функций в односвязной области Ω ⊂ C полная характеризация диагональных операторов получена Линчуком [1], Братищевым [2] (см. также [3; § 9]), Трибулой [4]. Доманский, Лангенбрух и Фогт [5]- [9] исследовали операторы адамаровского типа в пространстве вещественно аналитических функций на открытом множестве Ω ⊂ R 𝑁 .…”
Section: Introductionunclassified